Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Pearl Swaggerty Duckett with her sons Charles and Irvin Duckett); 1937 Huntington Beach, CA Pearl is the daughter of Mattie Watkins and Jim Swaggerty